2014
DOI: 10.5553/elr.000019
|View full text |Cite
|
Sign up to set email alerts
|

False Confessions in the Lab: A Review

Abstract: Intuitively, confession is a strong piece of evidence, because it appears unlikely that a suspect would confess to a crime he did not commit, thereby acting against his own best interest. Surprisingly, experimental studies show that innocent and well-educated individuals do tend to confess falsely when questioned about something they did not in fact do. In this contribution, an overview is presented of the experimental research on confession evidence. Limitations and implications of the scientific insights are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Both real-world cases and experimental research suggest that persuasion-based approaches are effective in generating confessions from suspects without having an overtly physical component (King & Snook, 2009; Meissner et al, 2014). The concern regarding the reliability of confessions remains, however, as such psychologically based tactics have also been implicated in convincing innocent suspects to confess falsely (Kassin & Gudjonsson, 2004; Rassin & Israëls, 2014; Russano, Meissner, Narchet, & Kassin, 2005). In recognition of this fact, a recent large scale survey of experts on the psychology of confessions found that they agreed uniformly that false confessions can be increased by minimization and false evidence ploys—two commonly used police tactics (Kassin et al, 2018).…”
Section: Perceptions Of Police Interrogationsmentioning
confidence: 99%
“…Both real-world cases and experimental research suggest that persuasion-based approaches are effective in generating confessions from suspects without having an overtly physical component (King & Snook, 2009; Meissner et al, 2014). The concern regarding the reliability of confessions remains, however, as such psychologically based tactics have also been implicated in convincing innocent suspects to confess falsely (Kassin & Gudjonsson, 2004; Rassin & Israëls, 2014; Russano, Meissner, Narchet, & Kassin, 2005). In recognition of this fact, a recent large scale survey of experts on the psychology of confessions found that they agreed uniformly that false confessions can be increased by minimization and false evidence ploys—two commonly used police tactics (Kassin et al, 2018).…”
Section: Perceptions Of Police Interrogationsmentioning
confidence: 99%
“…This confirms that a confession remains a strong piece of evidence in decision makers' perception. By contrast, experimental research suggests that confession evidence is not that strong, because innocent individuals can be brought to confess to a crime quite easily (see for overviews, Kassin, 2005;Rassin & Israëls, 2014).…”
Section: No Psychopathy Psychopathymentioning
confidence: 99%
“…One reason for this is that false confessions are a prominent source of wrongful convictions (Kassin, 2017). Although some scholars have asserted that there are important individual differences that might impact people's willingness to confess to a crime that they did not commit (e.g., Gudjonsson, 2010Gudjonsson, , 2018, other scholars have argued that individual differences do not play a significant role in the susceptibility to form false confessions (Israëls, 2011;Mergaerts, 2019;Rassin & Israëls, 2014).…”
Section: Introductionmentioning
confidence: 99%